20th Prof Vladas Gronskas International Scientific Conference. Abstract Book - Šarkiūnaitė, Ingrida; Ūsas, Antanas (Vilnius University Proceedings, 2026)
The “20th Prof. Vladas Gronskas International Scientific Conference” conference is an arena for cooperation and scholarly fellowship with young researchers and bachelor, master, and doctoral students from Lithuania and foreign countries. It is an arena for open discussion where young researchers can present and share their scientific insights. This conference encourages internationalization and closer cooperation between science and business. The conference keynote speakers – business representatives – provide participants with new insights and inspiration for further research. The main goal of this scientific gathering is to contribute to a reliable, safe, effective, and sustainable economy and business development. Encouraging entrepreneurship is a crucial condition for economic growth, and this puts forward a new approach to business, creativity, value creation, and innovation. It is precisely in this context that business and science should interact.
Keywords: international conference; entrepreneurship; economy and business development